Impact of Climate Change On Early Childhood Education In Mashonaland East Province of Zimbabwe - Jim, Ottiliah; Zishiri, Christopher; Samkange, Wellington (CV. Inara, 2025)
Global warming has become an international concern, since it has contributed to extreme climatic conditions in most parts of the world. This has been attributed to several factors that include industrialization resulting in carbon emission, deforestation and use of chemicals in agriculture. The changes in temperatures influence climate change. Climate change is increasingly disrupting the provision of education in most developing countries. Early childhood education is severely affected because of the ages involved, thus 3-8 years. The paper examined the effects of climate change on early childhood education in Mashonaland East Province of Zimbabwe. It is a region affected by recurrent droughts, erratic rainfall, and extreme temperatures. The paper examined how climate-induced environmental degradation, resource scarcity, and socio-economic instability affected access to safe learning spaces, disrupted educational activities, and hindered cognitive, emotional, and physical development in children. The paper is guided by Bronfenbrenner’s Ecological Systems Theory. The theory explains how multiple societal systems such as the microsystem, mesosystem, exosystem, macrosystem, and chronosystem influence child development. A qualitative research approach was employed. It involved assessing infrastructure vulnerabilities, attendance trends, and health outcomes in five purposively selected early childhood development centres in Mashonaland East Province. The case study design was used to study cases in the five selected centres. The paper explored how flooding, heat stress, and water shortages affected learning environments. The notable effects of climate change on young children were malnutrition, fear because of insecure environments, displacement, and trauma. The paper also examined local interventions and adaptive strategies, including school gardening, indigenous disaster-response practices, and mobile play-based learning initiatives during crises to sustain education and promote child development. Findings were that 60% of early childhood development centres experienced recurrent closures during extreme weather, and that food insecurity and caregiver displacement reduced school participation by 40%. The paper recommends integrating indigenous knowledge systems into policy, and investment in climate-resilient infrastructure, trauma-informed teacher training, and partnerships to enhance food and water security, and collective efforts to drill boreholes to enhance food production in drought prone areas.